SMS seed customers mining model and algorithm based on content analysis - Zhichao HUANG; Juncai TAO; Shengbao GAO (Dianxin kexue)
In order to mining SMS（short message service）seed customers from massive text messages，control the spread of the seed messages path and improve the efficiency of its spread，a SMS seed customers mining model and algorithm was proposed，which was based on content analysis. First of all，by analyzing the interest，randomness and one-way characteristics of customer forwarding messages，the tree model of customer forwarding messages were constructed. Secondly，the optimal seed customers mining model was generated by definition and application of comprehensive evaluation function，and SMS seed customers mining was realized based on the concept of close group. Finally，by analyzing the actual data from telecom operators，the effectivity of the model and algorithm was verified.